Safe Digital Spaces and Protection of Women’s Privacy: A study of Live Streaming Practices in a Private Algerian Feminist Group on Facebook - نذار خادم خلود; بوعدة حسينة (International Journal of Social Communication, 2025)
This study examines how Algerian women utilize the live streaming feature within a closed feminist Facebook group to explore interaction dynamics, forms of self-expression, and the boundaries of digital safety in virtual spaces shaped by feminist practices. The research adopts a qualitative approach, employing participant observation and focus group interviews as its primary methodological tools. The findings indicate that live streaming within this group functions not only as a communication medium but also as a mechanism for solidarity, emotional support, and the sharing of knowledge and information related to women’s issues. The closed and private nature of the group plays a crucial role in strengthening participants’ sense of digital safety, thereby encouraging relatively freer forms of expression compared to public online spaces. Nevertheless, the study reveals a persistent sense of caution among group members regarding identity disclosure and the sharing of sensitive views. This reflects a collective awareness of digital exposure risks, even within spaces perceived as “safe.” The study concludes that such closed feminist digital spaces constitute forms of alternative public spheres, digitally reconstructed by women in ways that prioritize privacy, protection, and collective safety.